Intra-seasonal contrasting trends in clouds due to warming induced circulation changes - S. S. Prijith (Nature Portfolio, 2021)
Abstract Quantification of long term changes in cloud distribution and properties is critical for the proper assessment of future climate. We show contrasting trends in cloud properties and cloud radiative effects over Northwest Indian Ocean (NWIO) in south Asian summer monsoon. Cloud top height (CTH) decreases in June (− 69 ± 3 myr−1) and July (− 44 ± 3 myr−1), whereas it increases in August (106 ± 2 myr−1) and September (37 ± 1 myr−1). These contrasting trends are investigated to be due to the changes in upper tropospheric winds and atmospheric circulation pattern. Strengthening of upper tropospheric easterlies and changes in vertical wind dampen the vertical development of clouds in June and July. In contrast, weakening of upper tropospheric winds over NWIO and strengthening of updraft favour the vertical growth of clouds in August. Further, changes in horizontal winds at 450–350 hPa and strengthening of Indian Ocean Walker cell favour the westward spread of high level clouds, contributing to the increase in CTH over NWIO in August. Decrease of cloud cover and altitude in June and July and increase of the same in subsequent months would affect the monsoon rainfall over the Indian region. Proper representation of these intra-seasonal contrasting trends of clouds in climate models is important for the better prediction of regional weather.